1994
DOI: 10.1002/lsm.1900150407
|View full text |Cite
|
Sign up to set email alerts
|

Erb:YAG and Hol:YAG Laser Osteotomy: The Effect of Laser Ablation on Bone Healing

Abstract: Sixty-nine male Sprague Dawley rats were divided into three groups of 23 animals each and osteotomies were performed in group 1 with a power saw, in group 2 with the Erb:Yag laser, and in group 3 with the Hol:YAG laser. Two animals of each group were sacrificed 1 week, 4, 8, and 12 weeks after operation for histologic investigation, and five animals of each group at 4, 8, and 12 weeks after osteotomy for torque testing. Anterior-posterior (AP) radiographs were taken at the same time points and investigated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 23 publications
(25 reference statements)
3
33
0
3
Order By: Relevance
“…Charlton et al 94 could demonstrate that the erbium laser caused a zone of secondary damage to surrounding tissue of about 5 µm, whereas this zone was greatly increased to 80 µm with significant charring in the case of holmium. Similar results were presented by Buchelt et al 95 In a histological and biomechanical (torque testing) study in rat tibiae, the authors compared bone healing after the use of an Er:YAG and Ho:YAG lasers with a power saw. Although Ho:YAG laser-treated osteotomies exhibited formation of dense fibrous tissue, carbonization, and no callus formation within 12 weeks, Er:YAG and saw osteotomies provoked a certain reunion within 8 weeks.…”
Section: Experimental Er: Yag Laser Osteotomysupporting
confidence: 65%
“…Charlton et al 94 could demonstrate that the erbium laser caused a zone of secondary damage to surrounding tissue of about 5 µm, whereas this zone was greatly increased to 80 µm with significant charring in the case of holmium. Similar results were presented by Buchelt et al 95 In a histological and biomechanical (torque testing) study in rat tibiae, the authors compared bone healing after the use of an Er:YAG and Ho:YAG lasers with a power saw. Although Ho:YAG laser-treated osteotomies exhibited formation of dense fibrous tissue, carbonization, and no callus formation within 12 weeks, Er:YAG and saw osteotomies provoked a certain reunion within 8 weeks.…”
Section: Experimental Er: Yag Laser Osteotomysupporting
confidence: 65%
“…In dentistry, Er:YAG laser has been suggested for various purposes [10][11][12][13][14]22]. Especially, in periodontal therapy, this laser may be used for hard and soft tissue treatments such as gingivectomy, periodontal pocket curettage, root surface debridement, and osseous recontouring and removal of diseased soft tissue during periodontal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In living specimen, we have demonstrated that no thermal damage occurs on cells immediately adjacent to the wounded area as seen by evidence of active cell surface enzymes. These results w^ould suggest that bone healing may not be impaired in femtosecond laser surgery as is the case with nanosecond lasers [3]. These results will need to be validated in vivo.…”
Section: Discussionmentioning
confidence: 87%